(3GdLOjO aj GdbhGYO hGdGYQGa GdehMOI GdGYJeGOGJ GdeSJfOQjI (B500 /s - (3GdUZjQ, MSGe GdOjf YHO GdZfjs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2004)
(3GdbhGYO GdLOjOI daMU GdeSJfOGJ heWGHbJgG hGLH GdHfc aj Cf jcTa cd GdYjhH GdeWGHbI JYOjd eOI aMU GdeSJfOGJ , aMU GdeSJfOGJ HeYjGQ LOjO JCcjO Mb GdHfc aj GSJWdGY QZHI GdYejd aj GdJfGRd Yf GdGNJdGaGJ GdeYGdLI GdJaUjdjI deSJfOGJ fbd GdHVGFY SfO GdTMf GdHMQj YHQ GdeMjWGJ , SfO GdTMf GdHMQj ZjQ bGHd ddJOGhd SfO GdTMf GdUGOQ HefGSHI eTGQWI GjLGQ SfO Gdfbd eJYOO GdhSGFW SfOGJ Gdfbd GdUGOQI Yf hcdGA GdTMf SfOGJ Gdfbd GdGNQi GdGMcGe GdJj GSJMOKJgG GdbhGYO hGdGYQGa GdehMOI GdGMcGe GdeSJMOKI deUdMI GdeSJajOs
(3edGMb (B: (3U(B. 152 (3; HjHdjhZQGajG (B:(3U(B.147s
Keywords: (3GdChQGb GdJLGQjIs; (3GdSfOGJ GdeGdjgs